Effectiveness of Lemongrass Gel on Pain Intensity and Salivary Cortisol Levels in Adolescent Girls with Primary Dysmenorrhea - Hadibrata, Nabila Febriana; Sumarni, Sri; Sunarjo, Lanny (Journal of Maternal and Child Health, 2025)
Background: Primary dysmenorrhea is menstrual pain caused by increased prostaglandins, which cause excessive uterine contractions. This condition is often experienced by adolescent girls and can cause stress and increased cortisol levels. One safe and easy-to-use non-pharmacological treatment is lemongrass gel (Cymbopogon citratus), which contains essential oils such as citral and geraniol, which have analgesic, anti-inflammatory, and antispasmodic properties. The purpose of this study was to determine the effectiveness of lemongrass gel on pain intensity and salivary cortisol levels in adolescent girls with primary dysmenorrhea.Subjects and Method: This was a randomized controlled trial. The study location was State Vocational High School 11 of Semarang. Data collection was conducted from June to July 2025. The intervention group was given 2 grams of 5% lemongrass gel twice daily for 3 days, and the control group was given hot cream. The dependent variables studied were pain intensity and salivary cortisol levels, while the independent variables were lemongrass gel and analgesic cream (Hot Cream). The analysis technique used a paired sample t-test.Results: The mean pain intensity in the intervention group after being given lemongrass gel was lower (Mean= 2.55; SD= 1.15) compared to before the intervention (Mean= 8.30; SD= 1.13) and was statistically significant (p <0.001). The average salivary cortisol level in the intervention group after being given lemongrass gel was lower (Mean= 12.15; SD= 3.30) compared to before the intervention (Mean= 21.91; SD= 8.05) and was statistically significant (p=0.008).Conclusion: The application of 5% lemongrass gel was proven to be effective in reducing pain intensity and salivary cortisol levels in adolescent girls with primary dysmenorrhea, making it a safe and practical non-pharmacological therapy alternative.